Evaluation of neutrophil phagocytic, complement functions, and cytokines expression among diabetic patients in Abuja, Nigeria - Muhammad Musa, Babandina; Mainasara, Abdullahi Suleiman; Bakare, Mustapha; Emeribe, Anthony Uchenna; Shuwa, Halima Ali; Haruna, Shamsuddeen; Muhammad, Aminu Said; Abdullahi, Idris Nasir (European Journal of Clinical and Experimental Medicine, 2019)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Inflammatory response in Diabetes Mellitus (DM) begins with chronic sub-clinical inflammations as a result of insulin resistance and activation of both innate and adaptive immune system as the disease progresses to complicated diabetes. Hence, the present study investigated the neutrophil phagocytic, complement function (CH50), and some cytokine profiles among diabetic and non-diabetic patients attending the National Hospital in Abuja, Nigeria. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. To evaluate the neutrophil phagocytic, complement function (CH50), and some cytokine profiles among post-operative septic diabetic and post-operative septic non-diabetic patients at the National Hospital in Abuja, Nigeria. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. Subjects were recruited by convenient sampling technique through interviewer-administered questionnaires. Subsequently, blood samples were collected. Fasting blood sugar (FBS) (mmol/L) was determined using glucose oxidase method. Neutrophil function test (Fmol/phag) was assayed using nitroblue tetrazolium reduction test (NBT). Hemolytic complement function (CH 50) test was conducted using serum harvested from sheep sensitized with human group (ORh D +ve) red blood cells. While serum Interleukin-4, -6, -10 and TNF- α were determined using Enzyme Linked Immunosorbent Assay (ELISA). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Mean ± Standard deviation (SD) of FBS concentration of 10.5 ± 1.3 (mmol/|L) among diabetic and 4.7 ± 0.9 (mmol/L) among non-diabetics was recorded. There is a decrease in neutrophil phagocytic function with a mean ± SD of 5.4 ± 2.1 (Fmol/ phag) in diabetics compared to 9.2 ± 2.1 (Fmol/phag) in non-diabetics. Similarly, complement (CH 50) function and C-reactive protein were significantly lower in diabetics when compared to non-diabetics (p<0.001). There was a significant difference in IL-6 concentration between diabetics and non-diabetics groups, but no significant difference was observed in TNF-α, IL-4 and IL-10 concentrations between study groups (p>0.05). TNF-α and IL-6 was significantly higher in diabetics with cardiovascular disorders compared to non-diabetics subjects with cardiovascular disorders (p<0.001). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Findings from this study revealed the association of complement, neutrophil phagocytic function, CRP and IL-6 among septic diabetic patients,. In addition TNF-α and IL-6 expression was higher in DM patients with cardiovascular disorders.